PENGARUH PERSEPSI DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN SABUN LIFEBUOY CAIR (STUDI KASUS PADA SANTRI PUTRI KELAS XI SMA AN-NUR BULULAWANGMALANG - erlinda bisri prastika; rini rahayu kurniati; daris zunaida (LPPM FIA Unisma Malang, 2020)
This research was conducted with the aim to find out how much influence the perception and quality of liquid Lifebuoy soap products on consumer loyalty. The method used in this study is a quantitative method, data collection techniques using a questionnaire. The results of this study are partially with the variable Perception (X1), Product Quality (X2) on Consumer Loyalty (Y) calculated using the T Test results that the Perception variable (X1) influences Consumer Loyalty, while the Product Quality variable (X2) has no effect on Consumer Loyalty (Y). Simultaneously with the variable Perception (X1) and Product Quality (X2) on Consumer Loyalty (Y) with multiple linear regression analysis there is a significant effect.